The analysis and reduction of starch in sugarcane by silencing ADP-glucose pyrophosphorylase and over-expressing β-amylase - Ferreira, Stephanus Johannes (Stellenbosch : University of Stellenbosch, 2008)
Thesis (MSc (Plant Biotechnology))--University of Stellenbosch, 2007.